Glicerina bruta melhora o valor nutricional de silagem de milheto colhido em duas idades - Machado, Samantha Mariana; Sales, Eleuza Clarete Junqueira de; Rigueria, João Paulo Sampaio; Pires, Daniel Ananias de Assis; Silva, Ariadne Freitas; Monção, Flávio Pinto (Agrarian, 2019)
The objective was to evaluate the best level of inclusion of crude glycerin in millet silage harvested at two cutting ages and its effects on the fermentation profile and nutritional value. The treatments consisted of the addition of glycerin during the ensilage millet (BRS 1502) in five inclusion doses in the natural material (0, 5, 10, 15 and 20%) and two cutting ages millet (60 and 80 days) following a completely randomized design in a 5 x 2 factorial scheme. The highest mean pH and ammoniacal nitrogen content of millet silage was observed in the control treatment at 80 days of age, with a mean of 3.33 (P = 0.02) and 6.09% of the total nitrogen (P <0.01), respectively. Millet silage harvested at 80 days and supplemented with 20% glycerin obtained higher dry matter content (P < 0.01; 28.3%), ethereal extract (P = 0.01; 8.5%), total digestible nutrients (P = 0.01; 76.8%) and digestible energy (P = 0.01; 3.4 Mcal/kg dry matter). Harvesting of the millet plant at 80 days associated with the use of 15% crude glycerin in the natural matter during silage improves the fermentation profile and the nutritional characteristics of the silage.